Collective Memory in International Relations 2021
DOI: 10.1093/oso/9780192895363.003.0001
|View full text |Cite
|
Sign up to set email alerts
|

Introduction

Abstract: ‘Memory—what a strange thing it is!…We can only think of it, in the line of an abstract time that is deprived of all thickness…Memories are motionless, and the more securely they are fixed in space, the sounder they are’, writes the philosopher Gaston Bachelard in ...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Focussing on the role of memories in the construction, reproduction, and contestation of political identities, IR research has shown how the past is used as a political and strategic tool to serve the present (Khong, 1992; Neustadt and May, 1986). Research has focussed on analysing how the memory of traumatic pasts guides states’ foreign policy behaviour (Bell, 2006; Budryte and Resende, 2013; Innes and Steele, 2014; Langenbacher and Shain, 2010; Zehfuss, 2007) and how (traumatic) collective memory has become one of the elements of identity that drive state policy (Bachleitner, 2021; Becker, 2013; Little and Rogers, 2017). Bachleitner (2019: 495) suggested the diplomacy of memory model as a specific foreign policy undertaking that consists of a ‘deliberate and coordinated diplomatic team effort to portray an official memory to the international stage’.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…Focussing on the role of memories in the construction, reproduction, and contestation of political identities, IR research has shown how the past is used as a political and strategic tool to serve the present (Khong, 1992; Neustadt and May, 1986). Research has focussed on analysing how the memory of traumatic pasts guides states’ foreign policy behaviour (Bell, 2006; Budryte and Resende, 2013; Innes and Steele, 2014; Langenbacher and Shain, 2010; Zehfuss, 2007) and how (traumatic) collective memory has become one of the elements of identity that drive state policy (Bachleitner, 2021; Becker, 2013; Little and Rogers, 2017). Bachleitner (2019: 495) suggested the diplomacy of memory model as a specific foreign policy undertaking that consists of a ‘deliberate and coordinated diplomatic team effort to portray an official memory to the international stage’.…”
Section: Analytical Frameworkmentioning
confidence: 99%
“…Sachiyo Tsukamoto’s The Politics of Trauma and Integrity contributes to a broad understanding of the state and its gendered subject dynamics by critically engaging with the interplay of narrative, memory and identity. Memory studies, at large, confront the multi-faceted exclusions and erasures against the power narratives (Bachleitner, 2021; Ranjan, 2023). Similarly, Tsukamoto adds new dimensions of history in this book by uncovering the marginalised truths (p. 2).…”
mentioning
confidence: 99%
“…Likewise, Michael Bernhard and Jan Kubik (2014) developed an influential typology of mnemonic regimes in East Central Europe by drawing on statements made by politicians and government officials. Others have analyzed how recall of the past has changed over time at the level of the state (Dixon 2018; Lebow, Kansteiner, and Fogu 2006; Mark 2011) and surveyed the ontological basis it provides for foreign policy (e.g., Bachleitner 2021), particularly among the former Warsaw Pact countries (Domańska 2022; Mälksoo 2009) and in East Asia (Wang 2012).…”
mentioning
confidence: 99%